Subclinical Ultrasound Characteristics of Infantile Hemangiomas That May Potentially Affect Involution. (8th September 2020) - McNab, María; García, Carolina; Tabak, Denise; Aranibar, Ligia; Castro, Ariel; Wortsman, Ximena
Abstract : Objectives: Infantile hemangiomas (IHs) are the most common benign tumors in children. Color Doppler ultrasound is a noninvasive imaging modality that can show subclinical anatomic parameters in a wide range of dermatologic conditions. The purpose of this study was to describe the ultrasound characteristics of IHs and look for subclinical features with the potential to influence the involution and therapeutic response. Methods: A review of the ultrasound database of children with clinical and ultrasound IH diagnoses was conducted. The clinically reported duration and the ultrasound assessment of the proliferative phase were compared. Descriptive and statistical analyses of qualitative and quantitative parameters of the series were performed. Significance was set at P < .05. Results: A total of 204 IHs were included. Twenty percent had arteriovenous shunts; 15% had afferent branches from main regional arteries; and almost 30% showed involvement of deep structures. Sixty‐one percent of IHs were in the head and neck. Deep hemangiomas showed significantly thicker lesional vessels. A prolonged proliferative stage was significantly associated with a higher presence of arteriovenous shunts and a higher peak systolic velocity of the arterial vessels (≥15 cm/s) within the lesions. Conclusions: Color Doppler ultrasound can support the detection of subclinical anatomic features that may potentially influence the involution and response to treatment of IHs. Some of these characteristics may serve as potential markers to predict and manage IHs in prolonged proliferative stages.